Novel detection method for chemiluminescence derived from the Kinase-Glo luminescent kinase assay platform: Advantages over traditional microplate luminometers - Ryan A.V. Bell (MethodsX, 2014)
The efficacy of cellular signal transduction is of paramount importance for the proper functioning of a cell and an organism as a whole. Protein kinases are responsible for much of this transmission and thus have been the focal point of extensive research. While there are numerous commercially available protein kinase assays, the Kinase-Glo luminescent kinase assay (Promega) provides an easy-to-use and high throughput platform for determining protein kinase activity. This assay is said to require the use of a microplate spectrophotometer capable of detecting a luminescent signal. This study shows that: • The ChemiGenius Bioimaging system (Syngene), typically used for visualizing chemiluminescence from Western blots, provides an alternative detection system for Kinase-Glo luminescence. • The novel detection system confers an advantage over traditional luminometers, in that it allows visualization of the luminescent wells, which allows for the real-time analysis and correction of experimental errors (i.e. bubble formation). • Determining kinase kinetics using this detection system produced comparable results to previous studies on the same enzyme (i.e. glycogen synthase kinase 3).